Choice Shifts in Groups: A Decision-Theoretic Basis - Eliaz, Kfir; Ray, Debraj; Razin, Ronny (American Economic Review, 2006)
The phenomenon of choice shifts in group decision-making has received attention in the social psychology literature. Faced with a risky group decision, individuals appear to support more extreme choices relative to those they would make on their own. This paper demonstrates that from a decision-theoretic perspective, choice shifts are intimately connected to failures of expected utility theory. In the model studied here, the Allais paradox is equivalent to a well-studied configuration of choice shifts. Thus, our results marry two well-known behavioral regularities, one in individual decision theory and another in the social psychology of groups.